Suprasellar granular cell tumor: A rare case report - Parmar , Vipal Hasmukhbhai; Parikh, Prashant Mahendrabhai; Mehta, Bhavana Asit; Shah, Sandip Chandrakant; Murnal, Ankita Girish (Eastern Journal of Medical Sciences, 2024)
Granular cell tumor (GCT) originating from the sellar and suprasellar regions, specifically from the neurohypophysis, is a rare neoplasm. Symptomatic GCT of the neurohypophysis is exceedingly rare, being